Experience of Preservation of Traditional Culture and Interaction between Society and State in National Parks of Austria (by Example of National Park “Hohe Tauern”) - P. A. Kurinskikh (Научный диалог)
On the example of the National Park “Hohe Tauern” some aspects of preservation of traditional culture in national parks of Austria are considered. The raised problem is the subject of interdisciplinary research: history, ethnocultural studies, ethnological regional studies, sociology. The relevance of the study is determined by the risks of loss of identity for a number of ethnic groups, the need to protect, preserve and present their traditional culture. Special attention is paid to the issues of correlation and revival of traditional knowledge, appeal to ethnic self-identification, obtaining economic benefits. The author traces the ways of solving these problems on the basis of the analysis of the experience gained in Austria in the organization of interaction between the population living in the national park, its management, the public and public authorities through the choice of special social technologies, including “folklorism.” Special attention is paid to the orientation of the country’s economy to increase the tourist flow. On the basis of the analysis of the problems the author came to a conclusion that the activities of the National Park “Hohe Tauern” most fully reflects the principles laid down by the Alpine Convention aimed at the development of recreational potential of the territory due to the disclosure of its historical and cultural potential. The experience of the National Park “Hohe Tauern” reflects the effectiveness of international legal documents in the field of sustainable long-term development at the micro level.